Effect of Flap Design for Enamel Matrix Derivative Application in Intraosseous Defects. (April 2021) - Trombelli, L.; Simonelli, A.; Quaranta, A.; Tu, Y.K.; Li, H.; Agusto, M.; Jiao, X.J.; Farina, R.
Objective: To systematically review the literature addressing the focused question: What is the effectiveness of different surgical and nonsurgical procedures combined with enamel matrix derivative (EMD) on clinical, radiographic, and patient-centered outcomes in intraosseous defects? Methods: Electronic (Medline, Scopus, and Cochrane databases) and hand literature searches were performed for studies including at least 1 treatment arm where EMD had been applied according to 1 of the following procedures: modified Widman flap; papilla preservation variants (PPVs), including papilla preservation technique, modified papilla preservation technique, and simplified papilla preservation technique; minimally invasive variants, including minimally invasive surgical approach and minimally invasive surgical technique; single-flap variants (SFVs), including single-flap approach and modified minimally invasive surgical technique; or nonsurgical application (flapless approach). Data from 42 selected articles were used to perform a network meta-analysis, and a hierarchy of surgical and nonsurgical applications of EMD was built separately for EMD and EMD + graft based on 6- to 12-mo clinical and radiographic outcomes. Results: Among surgical approaches, EMD was associated with best regenerative outcomes when applied through SFVs, with a mean clinical attachment level gain of 3.93 mm and a reduction in the intrabony component of the defect of 3.35 mm. For EMD + graft, limited differences in regenerative outcomes were observed among surgical procedures. PPVs were associated with the highest residual probing depth for EMD (4.08 mm) and EMD + graft (4.32 mm). Conclusions: In the treatment of periodontal intraosseous defects, 1) SFVs appear to optimize the regenerative outcomes of EMD; 2) substantial regenerative outcomes can be obtained with SFVs and conservative double flaps (i.e., PPVs and minimally invasive variants) when EMD is combined with a graft; and 3) residual probing depth was higher following PPVs for EMD and EMD + graft. Knowledge Transfer Statement: The results of the present systematic review and meta-analysis can be used by clinicians to identify the most effective surgical or nonsurgical procedure to treat an intraosseous defect with EMD or EMD + graft. The main findings indicate that when EMD application is indicated, surgical access based on a single flap seems the most appropriate to optimize clinical outcomes. The application of EMD + graft can be effectively combined with single flaps and conservative double flaps.